基于LMD和Lempel-Ziv指标的轴承径向磨损程度识别 - 何雷; 谭建平; 尹芳莉; 丁闯 (Jixie Chuandong, 2014)
For different wear of the bearing,a fault severity degree recognition scheme based on local mean decomposition（LMD）and Lempel-Ziv index is put forward.The vibration signal is decomposed by LMD,the optimal two PF components are selected and reconstructed according to kurtosis conditions,the normalized Lempel-Ziv values for the reconstruct signal envelope are calculated.Then the values multiplied by given weights are summed up to form a final measure named the integrated Lempel-Ziv index.Different intervals of the index value correspond to different fault severity.The bearing fault Lempel-Ziv index distribution rule at different load and rotating speed is studied.The experiment results show that the algorithm can be effectively applied in rolling bearing fault diagnosis and radial wear assessment of gearbox.